خطہ پوٹھوہار میں پنجابی زبان میں اولین ترجمہ قرآن از مولانا ہدایت اللہ:منہج و خصوصیات: First Punjabi Translation of The Holy Quran in Pothohar region by Maulana Hidayat ullah:Methodologh and characteristics - Dr.Abdul Ghafoor, (MEI, 2024)
To make the Holy Quran understandable for general public,the sub۔continent scholars translated the holy Quran in various languages.Scholars from the Punjab province translated the holy Quran in Punjabi language to understand the meaning of holy Quran.Maulana Muhammad bin Barak allah lakhvi translated the holy Quran in persion and Punjabi languages.Muhammad Suleman domailvi translated the holy Quran in poetic Punjabi.In Punjab mualana Hidayat ullah during his stay of Rawalpindi,he translated the holy Quran in Punjabi language in 1891. This translation was the first Punjabi translation of the holy Quran in Pothohar region,in which the Quranic teachings are clarified.Shah Abdul Qader Dehlavi was the 1st muslim scholar who translated the holy Quran in Urdu language idiomaticaly.This translation is considered as a reference in Urdu translations of the holy quran,as the translators after him used it in translations.Mualana Hidayat ullah fetched the feathers of his translation from shah Abdulqadir mohadis dehlyi,s Urdu translation.He got help from several other Punjabi translators.To highlight this translation to common person no one has done this effort.To highlight the feathers of the holy Quran in Punjabi this article written.In this article some characteristics of this Punjabi translation of the holy Quran are discussed.